FURIOUS PHILOSOPHY: ESSAY WITH CLARICE LISPECTOR’S ANGER (Muitas Vozes, 2021)
This essay deals with thinking philosophically the anger with Clarice Lispector. To this end, I consider more diverse aspects of the Lispector whole work that are affected by anger and then I focus specifically on the articles “Fartura e carência” and “Dies irae” to understand this angry way of thinking and feeling life. A brief conceptual history of anger is presented from the philosophical work of Seneca, Vilém Flusser and Peter Sloterdijk to better situate the issue and also to show that what Lispector thinks of anger is equally consistent, complex and furious as can be. Lispector elaborates a fictional bond with anger, she invents and reinvents ways to feel anger far from morality and sin, but close to indignation and contestation. There is no intention here to investigate a concept, theme or issue exhaustively enough to wear it out. The proposal is simply to philosophize with Lispector's anger and think about the issues of rage with the free form of the philosophical essay.